2000
DOI: 10.1093/jnci/92.19.1582
|View full text |Cite
|
Sign up to set email alerts
|

Health Outcomes After Prostatectomy or Radiotherapy for Prostate Cancer: Results From the Prostate Cancer Outcomes Study

Abstract: There are important differences in urinary, bowel, and sexual functions over 2 years after different treatments for clinically localized prostate cancer. In contrast to previous reports, these outcome differences reflect treatment delivered to a heterogeneous group of patients in diverse health care settings. These results provide comprehensive and representative information about long-term treatment complications to help guide and inform patients and clinicians about prostate cancer treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
282
5
13

Year Published

2003
2003
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 454 publications
(313 citation statements)
references
References 38 publications
13
282
5
13
Order By: Relevance
“…On the other hand, studies using the UCLA PCI concluded that RP impaired urinary condition. [17][18][19][20] This discrepancy with regard to our findings was due in part to the difference in instruments used. Although the UCLA PCI focuses on symptoms of irritability and incontinence, it is likely that patients with prostate cancer are bothered by bladder outlet obstruction as well as symptoms of irritability.…”
Section: Discussioncontrasting
confidence: 92%
See 1 more Smart Citation
“…On the other hand, studies using the UCLA PCI concluded that RP impaired urinary condition. [17][18][19][20] This discrepancy with regard to our findings was due in part to the difference in instruments used. Although the UCLA PCI focuses on symptoms of irritability and incontinence, it is likely that patients with prostate cancer are bothered by bladder outlet obstruction as well as symptoms of irritability.…”
Section: Discussioncontrasting
confidence: 92%
“…19,22,23 Rapid declines after surgery were followed by some improvement thereafter, but scores did not return to baseline levels. Several previous studies with the UCLA-PCI revealed similar trends, 19,22,23 and we conclude that this pattern of longitudinal change is typical of RP. In our study, XRT patients exhibited rapid declines of sexual function and increase in bothersomeness, and levels did not change thereafter.…”
Section: Discussionmentioning
confidence: 99%
“…Our result, therefore, supports the role of radical prostatectomy in improving overall and prostate-cancer specific survival. [40][41][42] There are several strengths to the results obtained in this current study. Primarily, the data used in this study was obtained from the NCI's SEER program, which accounts for 14% of the total US population and ascertains nearly all cancer patients in the designated SEER registries.…”
Section: Androgen Deprivation Therapy and Prostate Cancer Survival L mentioning
confidence: 77%
“…Furthermore, the great majority of patients receiving treatment for clinically localized prostate cancer ultimately die with, rather than of, their carcinoma. Therefore, the patients will have to live many years with the long-term effects of their treatment, 3 which may have adverse impact on the patients' QoL.…”
Section: Introductionmentioning
confidence: 99%